The Healthcare Chapel: Improving Well-being - Lawson Jr., Alvis E. (The international journal of religion and spirituality in society, 2021)
The role of contemporary healthcare is caring for the whole person: physically, mentally, and spiritually. These three portions of a whole person are not mutually exclusive, each having an effect on the other. The chapel functions as a place to enhance well-being through differing religious practices and thus contributing to meeting the needs of the whole person, providing a space for the spiritual care of the individual in healthcare facilities, augmenting the clinical care. The purpose of this research is to examine the architectural environment of the healthcare chapel, analyze the chapel’s effect in the process of healing for the patient, medical staff and the community, and for the demonstration of the need for meaningful and inclusive sacred spaces within the existing or future healthcare facility. Architectural requirements of differing religions (Christianity, Islam, Judaism, Buddhism, Hinduism, and Indigenous populations) are addressed in this research, focusing on appointments that would enhance well-being, the understanding of well-being as influenced by prayer, and concepts of sacredness. Through three case studies, qualitative research methods, including interviews, site observations, and document reviews, help to gain a deeper insight into the influence chapels have on the patient, medical staff, and community well-being. Data analysis reveals the reoccurring themes of a relevant architectural vocabulary with particularities to certain religions while highlighting overlapping functions. The findings of the research highlight design parameters for the successful impact of the chapel and/or prayer rooms, quiet spaces, meditation spaces, and stations in the healthcare chapel.